Legal Review of PT. Surya Foresta's Compliance In Registering Casual Workers With BPJS Employment Based On Law No. 24 of 2011 and PP No. 35 of 2021 - Apriliani, Selvi; Alfiany, Temmy Fitriah (Dinasti Research, 2025)
His research began with the problem of non-compliance of the company (PT. Surya Foresta) in providing social security protection to workers, especially casual daily workers. Law No. 24 of 2011 stipulates that every worker, including casual daily workers, contract workers, or permanent employees, must be registered in the BPJS Employment program. Government Regulation No. 35 of 2021 regulates fixed-term work agreements, outsourcing, working hours and rest times. The method used in compiling this research is the legal approach method of examining regulations governing workers' rights to BPJS employment and the empirical approach of observing and analyzing practices in companies related to compliance with these regulations. The results of the study explain that non-compliance in providing social security can cause workers not to get the legal protection they should, cause discomfort, health and safety risks without protection, and economic uncertainty in old age for workers and their families.